Heat-related injuries in Australian workplaces: Perspectives from health and safety representatives. (June 2020) - Varghese, Blesson M.; Hansen, Alana L.; Williams, Susan; Bi, Peng; Hanson-Easey, Scott; Barnett, Adrian G.; Heyworth, Jane S.; Sim, Malcolm R.; Rowett, Shelley; Nitschke, Monika; Di Corleto, Ross; Pisaniello, Dino L.
Graphical abstract: Highlights: Work-injury risk increases in hot weather and risk factors require investigation. We examined stakeholder perspectives to identify work-injury risks in hot weather. A survey of health and safety representatives examined heat risks and outcomes. A range of modifiable work and organisational risk factors were identified. Preventive efforts should encompass heat-related physical injuries as well as illness. Abstract: Introduction: Hot weather poses occupational health and safety concerns for people working in hot environments. It is known that work-related injuries increase during hot weather, yet there is an incomplete understanding of the underlying factors. Methods: A national online survey was conducted in Australia among health and safety representatives (HSRs) to better understand factors contributing to heat-related injuries in workplaces. Risk factors and preventive measures associated with reported injuries were identified using log-poisson regression models. Results: In total, 222 HSRs completed the survey. Overall, 43% reported that injuries or incidents caused by hot/very humid weather occur sometimes or often in their workplace. Factors found to be associated with reported heat-related injuries included 'the wearing of personal protective equipment (PPE)' which can hinder the loss of body heat, and 'inadequate resources and facilities'. 'Piece-rate workers' and 'new workers' were identified as being at high risk. The most frequently adopted preventive measures for outdoor and indoor workers were the provision of PPE (despite some identified issues) and access to cool drinking water. HSRs reported that less injuries occurred in hot weather among outdoor workers if work was rescheduled to cooler times and shade was provided; and in indoor environments where there was adequate ventilation, heat sources were shielded and workers were able to self-pace. Conclusion: Organisational issues, workplace hazards, personal factors and preventive measures, are all determinants of heat-related injuries in Australian workplaces. Wider adoption of identified prevention measures could reduce the incidence of heat-related injuries in outdoor and indoor workplaces.